Dokumentasi dan Analisis Nilai Pendidikan Karakter dalam Folklor Asal Usul Desa Patia, Kabupaten Pandeglang - Al Gadri, Henri Henriyan; Trisnawati, Trisnawati (Jurnal Artikula, 2021)
This study aims to document the folklore “The Origin of Patia Village”, Pandeglang Regency, as well as analyze the value of character education in the folklore. This study uses a qualitative method with a folklore approach. There are four stages passed in this research. The four stages are first, on-site pre-research stage, second stage of on-site research, third way of making folklore manuscripts for archiving and fourth analysis of the value of folklore character education. The results of this study are the documentation of the folklore "The Origin of Patia Village" which is the wealth and identity of a region or community group in the form of folklore and the discovery of character education values in the folklore "The Origin of Patia Village" which is beneficial for the community and for the world of education by make teaching materials in schools in order to support character education